2009
DOI: 10.1111/j.1528-1167.2009.02201.x
|View full text |Cite
|
Sign up to set email alerts
|

How accurate is ICD coding for epilepsy?

Abstract: SUMMARYPurpose: Assess the validity of ICD-9-CM and ICD-10 epilepsy coding from an emergency visit (ER) and a hospital discharge abstract database (DAD). Methods: Two separate sources of patient records were reviewed and validated. (1) Charts of patients admitted to our seizure monitoring unit over 2 years (n = 127, ICD-10 coded records) were reviewed. Sensitivity (Sn), specificity (Sp), and positive and negative predictive values (PPV and NPV) were calculated. (2) Random sample of charts for patients seen in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
182
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(188 citation statements)
references
References 16 publications
4
182
1
1
Order By: Relevance
“…18 The CPCSSN case definition for dementia performed better than those constructed from Quebec billing data (sensitivity of 12.9%-39.7%) 19 and Canadian administrative hospital discharge data (sensitivity of 32.3%-66.9%, specificity of 100.0%). 20 The epilepsy results were similar to definitions using administrative databases for various Canadian provinces (PPV of 75.5%-98.9%, NPV of 94.0%-97.4%), 21 and for definitions combining diagnoses and medications to identify epilepsy cases in a US managed care organization data system (PPV of 79.2%-84.1%). 22 Lastly, cases of parkinsonism validated in an American Veteran's Health Administration database showed strong PPV (81%) when using ICD-9 codes alone but had poor sensitivity (18.7%); sensitivity improved when ICD-9 codes and medications were combined (42.5%), but PPV suffered (53.3%).…”
Section: Overall Study Samplementioning
confidence: 50%
“…18 The CPCSSN case definition for dementia performed better than those constructed from Quebec billing data (sensitivity of 12.9%-39.7%) 19 and Canadian administrative hospital discharge data (sensitivity of 32.3%-66.9%, specificity of 100.0%). 20 The epilepsy results were similar to definitions using administrative databases for various Canadian provinces (PPV of 75.5%-98.9%, NPV of 94.0%-97.4%), 21 and for definitions combining diagnoses and medications to identify epilepsy cases in a US managed care organization data system (PPV of 79.2%-84.1%). 22 Lastly, cases of parkinsonism validated in an American Veteran's Health Administration database showed strong PPV (81%) when using ICD-9 codes alone but had poor sensitivity (18.7%); sensitivity improved when ICD-9 codes and medications were combined (42.5%), but PPV suffered (53.3%).…”
Section: Overall Study Samplementioning
confidence: 50%
“…Seizures were identified through emergency room and hospitalization records using validated ICD-9 and ICD-10 codes. 21,22 We then excluded records with invalid or inaccurate information and all patients younger than 18 years at the time of the seizure. We further excluded patients with a diagnosis of a brain tumor in the previous 5 years as occasionally patients with brain tumors undergo surgery because of focal neurologic deficits, the tumor's nature (e.g., malignancy), and not because their seizures are refractory to medical treatment.…”
Section: Methods Study Designmentioning
confidence: 99%
“…Previous epidemiologic studies [11][12][13][14] have found that these data sources have a high level of completeness and validity. Physicians must submit diagnostic codes (up to 3 per visit) to be reimbursed under the feefor-service insurance plan, and relatively few Alberta physicians (< 7%) are on alternate payment plans, compared with other Canadian provinces.…”
Section: Study Setting and Data Sourcesmentioning
confidence: 99%